Spatial and temporal changes of erosion in the black soil region of Northeast China from 2000 to 2020 - WANG Shihao, XU Xinliang, CAO Wei (Ziyuan Kexue, 2023)
[Objective] A comprehensive assessment of soil erosion in the black soil region of Northeast China is essential for deepening our understanding of issues such as the control of regional water and soil losses, anti-degeneration of black soil, preservation of land fertility, and safeguard of national food security. [Methods] Based on the Revised Universal Soil Loss Equation (RUSLE) and the Revised Wind Erosion Equation (RWEQ) models, this study comprehensively assessed the water and wind erosion on farmland in the black soil region of Northeast China from 2000 to 2020 and analyzed the current situation, the spatial and temporal change of soil erosion, and the influence of changes in land use. [Results] The results suggest that: (1) The degree of soil erosion on farmland in the black soil region of Northeast China was mainly slight, and water erosion was more severe than wind erosion. The Changbai Mountains region and the Liao River Plain have undergone relatively intensive water erosion, while the wind erosion in the Liao River Plain, the Greater Kinggan Mountains region, and the Songnen Plain was more intensive than in other sub-regions. (2) Water erosion showed a decreasing trend in the past 20 years, especially in the Liao River Plain. It increased firstly and then decreased in the two decades, and the second decade (2010-2020) has seen a certain extent of alleviation compared with the first decade (2000-2010). (3) Wind erosion showed a slowing trend in the past 20 years. The wind erosion in the Liao River Plain and the wind erosion region decreased more obviously. Wind erosion showed a significant interannual decrease first and then a small increase. (4) There were differences in the effects of cropland change on water erosion and wind erosion changes in the black soil region of Northeast China over the 20 years. Water erosion was mitigated in the areas of fallowing and reclamation, and increased in the areas of paddy and other cropland conversion; fallowing and urban expansion had a positive effect on mitigating wind erosion. The effects of cropland change on water and wind erosion changes were more obvious in the first decade than that in the second decade. [Conclusion] Soil erosion is caused by multiple factors, such as climate, topography, soil type, and human activities. This study provides some reference for soil erosion control and management in Northeast China. In the regions with severe erosion, we can adopt methods like zero tillage, cross ridge tillage, and straw mulching according to the local characteristics of soil erosion to slow down the process.